Saddled by the saddle nose: A case of wegener's granulomatosis - Kanathur Shilpa; Heera Ramesh; Sachin Somashekhar; B Leelavathy (Wolters Kluwer Medknow Publications, 2024)
Wegener's Granulomatosis with polyangiitis (GPA) is a systemic disease of unknown etiology characterized by necrotizing granulomatous inflammation, tissue necrosis, and variable degrees of vasculitis in small- and medium-sized blood vessels. The classical clinical triad consists of involvement of the upper airways, lungs, and kidneys. Saddle-nose deformity is a well-recognized complication of GPA but more commonly occurs due to leprosy, trauma, cocaine abuse, and sarcoidosis. Since this entity is not commonly encountered in our country, we present a unique case of a middle-aged woman presenting with saddle-nose deformity and the diagnostic dilemmas faced by us. This case is being reported due to its rarity in Indian literature.